2022
DOI: 10.1002/adfm.202111727
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Eliminating Water in Prussian Blue Cathode for Sodium‐Ion Batteries

Abstract: Prussian blue analogs (PBAs) are promising cathode materials for sodium‐ion batteries (SIBs) due to their low‐cost, similar energy density comparable with that of LiFePO4 in lithium‐ion batteries, and long cycle life. Nevertheless, crystal water (≈10 wt%) in PBAs from aqueous synthesis environments can bring significant side effects in real SIBs, especially for calendar life and high temperature storage performance. Therefore, it is of great importance to eliminate crystal water in PBAs for future commercial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
114
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(145 citation statements)
references
References 43 publications
(40 reference statements)
3
114
1
Order By: Relevance
“…From synchrotron XRD (figures S5 and S6), CP-PW undergoes the same phase transition from P2 1 /n to R 3 between 30 to 40 • C. Hence, the phase transition near RT for Na-rich PW is independent of the synthesis method. The existence of both structures for the same compound near to RT has not been reported previously, although the two structures have been reported independently at RT [7,13,15].…”
Section: Near Room Temperature Octahedral Tilt Transition In Pwmentioning
confidence: 64%
See 2 more Smart Citations
“…From synchrotron XRD (figures S5 and S6), CP-PW undergoes the same phase transition from P2 1 /n to R 3 between 30 to 40 • C. Hence, the phase transition near RT for Na-rich PW is independent of the synthesis method. The existence of both structures for the same compound near to RT has not been reported previously, although the two structures have been reported independently at RT [7,13,15].…”
Section: Near Room Temperature Octahedral Tilt Transition In Pwmentioning
confidence: 64%
“…In this case, the ND experiment used a larger sample volume compared to the XRD experiment (∼2 g vs ∼2 mg) potentially leading to lower heating efficiency through the whole sample. Previous work on Na 1.76 Fe[Fe(CN) 6 ]•2.6H 2 O revealed that the cubic Fm 3m phase appears at 150 • C when heated at 3 • C min −1 and continues to coexist with a high-temperature R 3 phase until 300 • C [15].…”
Section: Variable Temperature Studies Of Pwmentioning
confidence: 98%
See 1 more Smart Citation
“…Crystal water in organic battery systems is generally considered to have a negative effect on electrochemical performance . However, a new discovery was found in K 2 [(VOHPO 4 ) 2 (C 2 O 4 )]·4.5H 2 O for MIBs.…”
Section: Magnesium-ion Batteriesmentioning
confidence: 99%
“…In some cases studies have reported that reducing the water content in PBAs leads to more stable cycling performance, whereas others report that the presence of water leads to a higher capacity. [16][17][18][19] Thus, further work is required for clarity regarding the role of guest water species on sodium ion mobility and cycling reversibility. The present paper seeks to demonstrate the beneficial effect of water removal on the sodium mobility and improvement of the cycling stability using Berlin green (BG).…”
Section: Introductionmentioning
confidence: 99%